Surface phosphatization of cerium-lanthanum oxides for catalytically inert white pigments - Onoda, Hiroaki; Wada, Takuma; Charoonsuk, Thitirat; Pulphol, Phieraya; Muanghlua, Rangson; Vittayakorn, Naratip (My University, 2025)
Cerium dioxide (CeO2) is a UV-scattering agent commonly employed in sunscreens but suffers from oxidative catalytic activity, raising concerns for dermal applications. To address this issue, surface passivation via phosphatization has been explored, although prior attempts with CeO2 alone failed to eliminate its intrinsic yellow hue due to low reactivity with phosphoric acid. In this study, we introduce a novel white pigment synthesized via the phosphoric acid-mediated treatment of CeO2–La2O3 mixtures. By co-utilizing lanthanum oxide, which readily forms lanthanum phosphate—a white, inert compound—we achieved enhanced suppression of oxidative activity alongside improved whiteness. The composite materials were systematically characterized via X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), particle size analysis, colorimetry (Lab*), and catalytic activity assays. The results reveal that phosphatization preferentially proceeds at lanthanum sites, forming phosphate-rich surface layers that diminish redox activity while maintaining favorable dispersion and smoothness properties. The pigment shows high acid resistance and negligible photocatalytic activity, indicating its potential as a safe, non-reactive alternative for cosmetic formulations. This work advances the development of rare-earth-based functional pigments via a scalable, low-temperature route.
Keywords: Cerium dioxide; Cosmetic pigments; Inorganic phosphate; Oxidation catalytic activity